Postirradiation osteosarcoma of the occipital bone: A case report (Indian Journal of Case Reports, 2018)
Postirradiation osteosarcoma is an uncommon complication of radiation treatment for brain tumors. It is associated with a poor prognosis and survival is usually <1 year. Herein, we report the case of a 58-year-old gentleman, who developed osteosarcoma of the occipital bone 5 years after the radiation treatment of oligodendroglioma in the right temporal lobe. He was treated for oligodendroglioma with surgery and radiation using two-dimensional radiation therapy technique to a total dose of 54 Gy through two lateral portals in two phases. Secondary osteosarcoma of the occipital bone occurred 5 years later on the ipsilateral side but within the previous field of irradiation. After metastatic workup, the patient was treated with surgery and adjuvant chemotherapy, but there was a progression of the disease after 6 cycles and the patient died 8 months after the diagnosis.